Prospective Ways of Electrical Sorting Devices - PHD R.Siddiqov; PHD. I. Usmanov; Mirzayev Islombek Umarali ogli; Abdusattorov Axadjon Ortiqali ogli; Alijonov Habibullo (Global Scientific Publishing, 2023)
Sorting of seeds of agricultural crops allows to reduce the consumption of seeds planted on land, to ensure uniform and smooth germination of seeds, to increase productivity and to reduce the cost of cultivated products. In order to carry out these works, it is necessary to use energy and resources wisely, to develop technology and technical means that save them. In the article, among other agrotechnical measures, in order to obtain a high yield from agricultural crops, the principles of operation of electric sorting devices are developed to improve the quality indicators of seeds prepared for planting, to obtain seeds with similar biological properties, high fertility and potential yield in laboratory and field conditions. and the results of the study of work bodies are presented
Keywords: Electric sorter device; melon seed